As especificidades da mercadoria força de trabalho: Marx revisitado - Antonio Vieira, Pedro (The specifities of the labor power commodity: Marx revisited (the labor power commodity: Marx revisited., 2012)
Coming along with Polanyi's ideas of fictitious commodity, this paper seeks to reveal the logical inconsistencies and silents in the economic science arguments on the labor force as a commodity. Once Marx's influence on the anti-capitalist movements is outstanding, we need to show his contribution, through his economic thought, to the scientific economism. As is well known, when proposed that the commodity sell by the worker was the 'labor force' instead the labor, as the classical economists used to say, Marx was able to built his theory on the capitalist economy theory, which relies on the concept of surplus value.. That is the reason why the paper is specially concern with the failures or weaknesses present in one of the huge Marx contribution to the economics thought: the concept of labor force. (English)
Economics
Keywords: MARX; Karl; 1818-1883; anti-globalization movement; capitalists & financiers; commercial products; economics; economism; economists; fictitious commodities; labor force; labor supply; labor-market; labour force; labour market; labour supply; political economy

Karl Polanyi E O ‘Grande Debate’ Entre Substantivistas E Formalistas Na Antropologia Econômica (Karl Polanyi and the 'Great Debate' Between the Substantivists and Formalists in Economic Anthropology) - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2012)
Na raiz do pensamento Polanyiano, encontra-se a distinção entre economia no sentido substantivo e economia no sentido formal. Com efeito, a concepção substantivista que define a economia como um processo instituído de interação entre o homem e o ambiente natural e social que o rodeia e resulta em contínua oferta de meios para satisfazer as necessidades humanas constitui a base do método preconizado pelo autor: a análise institucional. Com tal distinção, Polanyi (1977a) pretende evitar a "falácia economicista" que consiste na identificação automática da economia com sua forma de mercado. Ao contrário, só na moderna economia capitalista é que um "sistema de mercados formadores de preços" desempenha papel fundamental. Essas questões foram alvo de um "Grande Debate" entre as correntes substantivista – encabeçada por Polanyi – e formalista no contexto da disciplina da Antropologia Econômica.At the root of Polanyian thought, a distintiction can be found between the substantive and formal concepts of the economy. In fact, the substantivist conception, that defines the economy as an instituted process of interaction between man and its natural and social environment, which results in a continuous supply of material means to meet human needs, constitutes the basis of the method recomended by the author: institutional analysis. With this distinction, Polanyi intends to avoid the "economistic fallacy", which consists of the automatic identification of the economy in its market form. Only in the modern capitalist economy does a system of "price-making markets" play a fundamental role. These questions were amply discussed in the so-called "Great Debate" between the substantivist and formalist schools of thought in the discipline of Economic Anthropology. in Economia e Sociedade, Vol. 21, No. 1 (44), pp. 165-195
Sociology; Anthropology
Keywords: economy; formalism; institutional analysis; market; substantivism